THE EFFECT OF GREEN ACCOUNTING, CAPITAL STRUCTURE, LIQUIDITY, TOTAL ASSET TURNOVER, AND INVENTORY TURNOVER ON FIRM FINANCIAL PERFORMANCE - Ratna Niandra; Sriwati Sriwati (Graduate Program of Universitas Tarumanagara, 2026)
This research was conducted with the aim of providing empirical evidence on the extent to which the application of green accounting, capital structure, liquidity, total asset turnover, and inventory turnover affect the financial performance of companies in the consumer cyclical and consumer non-cyclical sectors listed on the Indonesia Stock Exchange during the 2022–2024 period. The research sample was obtained through the application of purposive sampling technique, which produced 186 observation data as analysis material. The data processing process in this study was carried out using the multiple regression analysis with the support of the EViews 12 SV statistical application. The results of the study show that green accounting has a significant negative effect on financial performance. The capital structure is also significant and negative. In contrast, liquidity has no significant effect on financial performance. Meanwhile, the total asset turnover has a significant positive effect on financial performance. On the other hand, inventory turnover also has a significant positive effect on financial performance.